Sigmoid Volvulus in Acromegalic Patient; Successful Surgical Management of Sigmoid Volvulus and Pituitary Macroadenoma: A Case Report - Chowdhury, Forhad H; Kawsar, Khandkar A; Kawsar, Khandkar A; Haque, Mohammod R; Haque, Mohammod R; Haque, AFMM; Haque, AFMM (Journal of Medicine, 2014)
Sigmoid volvulus in acromegalic patients is very rare. Here we report a case of sigmoid volvulus in an acromegalic patient who refused surgical treatment for pituitary macroadenoma after initial diagnosis five years back. Sigmoid volvulus was managed successfully by emergency laparotomy and sigmoid colectomy followed by primary end to end anastomosis. Six weeks later she underwent endonasal transsphenoidal removal of pituitary tumor. Postoperatively she improved gradaully and Post operative MRI of brain showed no residual tumor but still her serum GH level is high even after 12 months. So we advised her for radiotherapy. She is scheduled for regular follow up with clinical and investigational assessments. DOI: http://dx.doi.org/10.3329/jom.v15i1.19882 J Medicine 2014; 15: 84-86